Safety and efficacy of salvage low-dose-rate brachytherapy for prostate bed recurrences following radical prostatectomy - Kumar, Aryavarta M.S. (J Contemp Brachytherapy, 2015)
PURPOSE: To report efficacy in our series of nodular recurrences in the post-surgical bed that underwent salvage low-dose-rate (LDR) brachytherapy. MATERIAL AND METHODS: Patients with radical prostatectomy (RP) who had biochemical failure with nodular recurrence detected by DRE, ultrasound, and pelvic CT and then salvaged with LDR (125)I brachytherapy were included. Nodular recurrences were biopsy confirmed adenocarcinoma, and patients had no evidence of nodal or distant metastasis on imaging including bone scan. Follow up was at least every 6 months with a serial prostate specific antigen (PSA). RESULTS: Twelve patients had salvage LDR brachytherapy with median age 69 years (range 59-86) and median pre-salvage PSA of 4.22 ng/ml. Nodule biopsy Gleason score was 7, 8, or undifferentiated. Median rectal V(100) was 0.00 cc. Compared to pre-salvage, patients reported no additional genitourinary (GU) toxicity. After a median 35 months post-salvage follow up (range 10-81 months), patients had a median PSA nadir of 0.72 ng/ml (range 0.01-22.4). At 6 months post salvage, 90% of patients had a PSA below pre-salvage levels. At last follow up, 4 patients had PSA control. CONCLUSIONS: There was a trend to improved biochemical relapse free survival for lower Gleason score and pre-salvage PSA, which may be indicative of the lack of or only low volume metastatic disease. LDR brachytherapy is an effective salvage technique and can be considered in well selected patients allowing for dose escalation to the nodular recurrence.